Pemeriksaan Ante dan Post Mortem Hewan Kurban di Musholla Al Atqiyah Kota Mataram - Kholik, Kholik; Pradana, Munawer; Riwu, Katty Hendriana Priscilia; Kurnia, Rofi; Pratiwi, Dhea Siskha (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
The Faculty of Veterinary Medicine, UNDIKMA, in collaboration with the Al-Atqiyah Mosque in Mataram City, conducted an inspection of sacrificial animals on Eid al-Adha. The inspection aims to provide a sense of security to the public with ASUH meat products. The inspection of sacrificial animals includes a health inspection before slaughter (ante-mortem) and then continued with an inspection after the sacrificial animals are slaughtered (post-mortem). The inspection of sacrificial animals was carried out from June 6 to 7, 2025. The inspection of sacrificial animals was carried out on 14 sacrificial animals consisting of 3 cows and 11 goats. The ante-mortem inspection found that the 14 sacrificial animals were in healthy condition. The results of the post-mortem examination of the liver, heart, spleen, lungs, and kidneys did not find any organ changes and lesions from the characteristics of infectious or zoonotic diseases. In the post-mortem examination, only Fasciola sp worms were found in 15.38% of the 14 sacrificial animals examined. Fasciola sp was found in one cow (33.33%) of the 3 cows examined and Fasciola sp was also found in only one goat (9.09%) of the 11 goats examined, so the sacrificial meat is suitable for public consumption.
Keywords: ante-mortem; mataram; post-mortem; sacrifice